LA SOLUTION IMPLICITE DE CHARLES TAYLOR AU PROBLÈME DE L'« HISTORICISME TRANSCENDANTAL ». - St-Laurent, Guillaume (Symposium: Canadian Journal of Continental Philosophy / Revue Canadienne de Philosophie Continentale)
Our aim is to show that Charles Taylor's theory of philosophical argumentation proposes an elegant, albeit implicit, solution to the problem of "transcendental historicism" in contemporary hermeneutics (Heidegger, Gadamer, Ricoeur). This problem consists in asking how it is possible both to (1) disavow the existence of "absolute" or "anhistorical" truths and (2) fully acknowledge the status of philosophical discourses on "historicity" (Geschichtlichkeit), since those discourses remain de facto and de jure properly a priori. The following discussion focusses on how Taylor manages to justify the seemingly contradictory thesis that philosophical reflection can reach conclusions that are "apodictic and yet open to endless debate."